Pengaruh Arang Sekam Padi Terhadap Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascolanicum.L) - Handayani, Rizky; Lufita Nur Alfiah,; Rizah Rizwana Wahyuni, (SUNGKAI, 2024)
RIZKI HANDAYANI, NIM 1827028. "The Effect of Giving Rice Husk Charcoal on the Growth and Production of Shallot Plants (Allium ascolanicum. L)". Supervised by Lufita Nur Alfiah, SP., M.Si and Rizah Rizwana Wahyuni, S.TP., M.Sc. Onion (Allium ascalonicum L) is a horticultural plant belonging to the vegetable and spice group as a food flavoring. Shallots are one of the leading vegetable commodities that have been intensively cultivated by farmers for a long time. Acidic soil is soil that has a low pH, generally acidic soil will reduce the level of land productivity for some plants. Soil conditions with low productivity levels require the addition of ameliorant. The ameliorant that can be used is rice husk charcoal. Rice husk charcoal can be used to improve the place where a plant grows and can function as a builder of soil fertility. This research was conducted to determine the effect of giving various doses of rice husk charcoal on the growth and production of shallot plants. This research was carried out at the Kassa House of the Faculty of Agriculture, Pasir Pengaraian University from May to August 2022. The design used in the study was a Completely Randomized Design (CRD) with 5 treatments, namely R0 = 0 g/polybag, R1 = 20 g/polybag , R2 = 40 g/polybag, R3 = 60 g/polybag, and R4 = 80 g/polybag. The results showed that the results were not significantly different with the administration of several doses of rice husk charcoal on all observation parameters. Parameters of plant height and fresh weight of tubers tended to be higher by administering a dose of rice husk charcoal 80 g/polybag. While administration at a dose of 40 g/polybag tends to be higher for the number of tubers planted compared to other doses.